Validation of the name Garcinia leptophylla (Clusiaceae) - Bittrich, Volker; Marinho, Lucas C. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
During the continuous production of the “Catálogo de plantas e fungos do Brasil” (2010), some new combinations under Garcinia were proposed; however, they are invalid, since the respective basionyms were not indicated. Here, we propose the validation of the name Garcinia leptophylla Bittrich, a new name proposed for Rheedia longifolia Planch. & Triana. A lectotype for the name is also designated.